Physicochemical properties, antioxidant, and antibacterial activities of Premna serratifolia extract via cold extraction method - T., Saptu; Tan, L. L.; Awang Ahmad Sallehin, Awang Husaini; S. D., Ramaiya; I., HarunI; U., Utra; D., Silvia; Y. A., YusoF; K., Mahmood; N. N. A. K., Shah; Hanisah Kamilah, Abd Razak (IOP Publishing Ltd, 2025)
Premna serratifolia or ‘buas-buas’ is one of the common traditional herbs among Malaysians, well-known for its various benefits as traditional medicine. Out of 3000 Malaysian herbs, P. serratifolia is known as one of the potential herbs. P. serratifolia can be found in their native habitats in Borneo, especially in Sabah and Sarawak. The antimicrobial, antioxidant, and physiochemical properties of P. serratifolia extract were investigated in this study. A cold extraction method by using distilled water as a solvent was used to obtain the extract of P. serratifolia. The physicochemical properties of the extract, such as pH, colour analyses, moisture, total ash content, DPPH radical scavenging assay, antibacterial activity, FTIR, and GC-MS, were evaluated. The pH value, moisture content, and total ash content of the extract were pH 4.89, 0.77%, and 0.04%, respectively. There is an inhibition zone (7.9 mm-9.4 mm) in the antibacterial activity of P. serratifolia extract against E. coli. The scavenging activities, however, ranged from 59.8 to 89.9%, with an IC50, or half maximum inhibitory concentration, of 42.23 mg/ml. The GC-MS analysis of the P. serratifolia cold extract detected 27 compounds that have reported bioactivities. The major compounds found in this plant extract were 1,2-cyclopentanedione and 2,3-dihydro-benzofuran.